Atmosphere, Architecture, Cinema Thematic Reflections on Ambiance and Place - Tawa, Michael (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Atmosphere, Cinema, Architecture: Thematic Reflections on Ambiance and Place explores cinema and architecture as ambient and affective settings or circumstances that can enable the emergence of atmosphere. This book is an interdisciplinary reading of cinematographic practice which develops useful implications for spatial composition in art and architectural design. The way a film is set up, directed, composed, framed, and technically constructed can provide parallels, analogies and metaphors for the spatial organisation of cities, landscapes and buildings. Likewise, the way a built setting is conceived and devised can inform approaches to framing and spatial organisation in cinematography. The book begins on a personal note with a series of recollected atmospheric experiences, leading to an investigation of ambiguity and consilient discrepancy as circumstantial conditions necessary for the production of atmosphere. The mood of melancholia is explored to show the pivotal role that ambiguity, discrepancy and irresolution play in its distinctive ambiance. Atmosphere is then defined as an emergent condition arising between an ambient, affective circumstance and a mooded human being. The book then moves to analyse the inherent conditions in the setup of filmic and architectural settings that render them atmospheric. Reference is made to the cinema of Bresson, Resnais, Lynch, Tarr, Malik and Campion, and to Romanesque tympanae, the architectonic scenography of Franz Kafka's novel The Castle and the work of Spanish architects Flores Prats. The concluding section, Anatomy of Atmosphere, is a lexicon of concepts, themes and tactics around atmosphere that might usefully inform creative practice. Michael Tawa is an architect and Professor of Architecture in the School of Architecture, Design and Planning at the University of Sydney, Australia. He is the author of Agencies of the Frame: Tectonic Strategies in Cinema and Architecture and Theorising the Project: A Thematic Approach to Architectural Design. .
1. Rehearsing Atmospheres -- 2. Ambience -- 3. Mood -- 4. Atmosphere -- 5. Tectonics of Cinematic Atmosphere -- 6. Tectonics of Architectural Atmosphere -- 7. Anatomy of Atmosphere.
Keywords: Motion pictures; Design; Film Theory; Design